Análise de envoltória e do sistema de iluminação a partir do Regulamentotécnico da qualidade para eficiência energética de edifícios comerciais, deserviços e públicos para avaliação de desempenho de sistemas de fachada e de proteções solares. - Iara Goncalves dos Santos (2009)
Legislation about energy consumption of buildings is an important mechanism of the sustainability promotion for the built environment. The first governmental Brazilian instrument, from 2009 is the Technical Quality Legislation of the Level of Energy Efficiency of Commercial, Service and Public Buildings, RTQ-C. It classifies the global performance of buildings through the individual performance of the building envelope, the illumination system and the air conditioning system. The aim of this work is to study this Legislation by applying it to a public building in Belo Horizonte city. The building envelope and its illumination system are analyzed by studying a typical office configuration through the prescriptive method of the RTQ-C and also by thermal-energetic simulation using Energy Plus and Design Builder softwares. Parametrical analysis was carried out of the façade system, compounded partly by double glazing and partly by glazing over a cement plaque. The glass types of the apertures were varied; the glazing and cement plaque part of the façade was substituted by masonry and solar shading devices were introduced in the apertures. The solar protections were defined following two principles: by the better combination of vertical and horizontal angles in order to generate a minimum Consumption Index (IC) according to the prescriptive method of the RTQ-C and by the Neutral Temperature (Tn) Method. Furthermore, the original façade was simulated using two approaches. In the first one, the multiples layers of the façade glass, air and cement plaque were represented by a single surface with an equivalent thermal transmittance. In the second one, the layers were modeled as individual thermal zones, which allowed a better precision in obtaining the thermal effect of the glass layer in the façade system. From the prescriptive analysis of the RTQ-C, the envelope of the whole building was classified C and the lighting system of the office was classified B. From these results, changes in the building were proposed and discussed in order that both could obtain an A classification. In the simulation process, the main results showed that low-e gazing with high light transmittance raised the energy consumption if compared to the originally specified sun control glazing, when installed without solar shading devices, but showed to be the system with better natural light admittance. The masonry façade presented a higher performance than the glass-cement one, showing up to 13% less energy consumption when combined with solar shading devices when compared to the façade system originally proposed. Finally, the results of the simulation of the façade using an equivalent transmittance and using thermal zones were so divergent that one has to consider the need of differently approaching this kind of system in the prescriptive method of the RTQ-C.